THEORETICAL AND PRACTICAL STUDY OF SOME SURFACTANTS AND USE IN TREATMENT OF WATER IN CRUDE OIL (W/O) EMULSIONS - Al-Assadi, Muhanned; Dhumad, Adil (Iraqi Journal of Science, 2024)
Four types of surfactants derivatives of phthalic anhydride and alkyl amines consist of different length of hydrocarbon chains were prepared. The prepared surfactants were characterized by Infrared spectrophotometer and CHN analysis. The physical properties of the prepared de-emulsifiers were measured i.e. (pH, density, viscosity, CMC, molar conductivity and flash point). The efficiency of the prepared de-emulsifiers were studied with time and long side chain substituted. The hydrophilic-lipophilic balance (HLB) was calculated. The polarizability and dipole moment were studied by PM3 quantum mechanical method using the Hyperchem series program. The theoretical results were compared with the practical results